Crystallization effects of carbon nanotubes in polyamide 12 - Johnson, Rolfe Bradley (Georgia Institute of Technology, 2010)
Multi-walled carbon nanotubes (MWNTs) are a nanofiller that has desirable multifunctional properties. They have been shown to offer improved mechanical, thermal, and electrical properties in composites. Research has been studying their incorporation into polymer composites. Polyamide 12 is a polyamide of interest that has been manufactured to have lower moisture absorption and higher ductility than other commercial polyamides such as 6 and 6,6 at room temperature. In these studies, MWNTs have been incorporated into polyamide 12 at different weight loadings and using MWNTs with differing outer diameters. The composites were melt processed and characterized using differential scanning calorimetry (DSC) to understand the effects of MWNTs on the crystallization behavior of polyamide 12. A melt peak splitting behavior was observed in the polyamide 12 and composite samples when the specimens were not allowed to fully anneal. Total crystallinity in the samples remained the same between the polyamide 12 and composites when the samples were fully annealed. Total crystallinity increased by 1 to 4 percent in the composites over the polyamide 12 when samples were not fully annealed. The addition of MWNTs to the polyamide 12 system increased the amount of crystallization contained in the lower temperature melting peak. An increase in MWNT concentration resulted in an increase in the crystallinity contained in the lower temperature peak. The addition of smaller diameter MWNTs resulted in a further increase in the lower temperature peak when the outer diameter was below a critical size.